Automatic ER and PR scoring in Immunohistochemistry H-DAB Breast Cancer images - Rogalsky, Johanna Elisabeth; Ioshii, Sergio Ossamu; Oliveira, Lucas Ferrari de (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2021)
Breast Cancer (BC) is the most frequently diagnosed cancer for women. This way, the Brazilian Uniﬁed Health System (SUS) focuses on studying the disease and improving all the steps involved in dealing with BC. The presence or absence of the Estrogen Receptor (ER) and the Progesterone Receptor (PR), which deﬁne invasive subtypes, is detected through Immunohistochemistry (IHC). One way to assist the manual assessment of pathologists and histopathologists is to develop automatic scoring systems. Fortunately, digital pathology is increasingly achieving higher agreement with the pathologist. Therefore we create an automatic scoring system composed of image preprocessing, feature extracting, and classiﬁcation achieves a 69% f-score rate.